Prospective Audit to Study urokinaSe use to restore Patency in Occluded centRal venous caTheters in haematology and oncology patients (PASSPORT 2). Issue 4 (July 2021) - Kumwenda, Mick John; Dougherty, Lisa; Jackson, Andrew; Hill, Steve
Background: Central venous catheter dysfunction may be associated with intraluminal clots, drug precipitates and lipid residues or extra luminal causes such as fibroblastic sleeve, tip malposition, pinch-off syndrome and venous thrombosis at the tip of central venous catheter. Failure to restore patency after addressing these causes, empirical treatment with thrombolytic agents should be considered. Urokinase is used widely as a thrombolytic agent but very few outcome studies have been published. Methods: A multicentre group conducted a prospective audit of management of central venous catheter dysfunction after exclusion of common causes using in centre standardised doses of urokinase from September 2017 to February 2018 in haematology and oncology units. Data of catheter blood flow were collected anonymously following administration of 5000- to 25, 000-IU urokinase in dysfunctional central venous catheter. Results: A total of 117 patients were recruited from eight centres, 54 females and 63 males, median age was 60 (46–68). In total, 53% presented as partial withdrawal occlusion and 47% total occlusion. In partial withdrawal occlusion, patency was restored in 80% of interventions, in 82% of interventions using push lock and in 76% using dwell lock. In total occlusion, patency was restored in 88% of the interventions. The central venous catheter clearance rate was dose dependent; patency was restored in 83% of central venous catheter with 5000 IU, 89% with 10, 000 IU and 92% with high dose of 25, 000 IU. No adverse events were recorded. Conclusion: In this study, treatment of dysfunctional central venous catheter using standardised urokinase doses was safe and effective in restoring patency when no other mechanical causes could account for central venous catheter dysfunction.